Mathematical Model to Predict the Permeability of Water Transport in Concrete Structure - Eluozo, Solomon Ndubuisi (International Journal of Sustainable Construction Engineering and Technology, 2013)
Mathematical model to predict the permeability of water transport in concrete has been established, the model is to monitor the rate of water transport in concrete structure. The process of this water transport is based on the constituent in the mixture of concrete. Permeability established a relation on the influence of the micropores on the constituent that made of concrete, the method of concrete placement determine the rate of permeability deposition in concrete structure, permeability establishment are under the influence of the micropore between the constituent  through the cement paste,  coarse  aggregate fine sand and water, the  micropore between this material as a component of concrete are  known as porosity and void ratio in the concrete structure, the influence of the permeability coefficient determine the rate of water transport in concrete, considering the variables in the system,  mathematical model were established to  monitor the rate of water passing through concrete and also determine the rate of permeability coefficient on concrete structure.